2005
DOI: 10.1111/j.1745-7254.2005.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-dependent apoptosis induced by a novel amphipathic photochemotherapeutic agent ZnPcS2P2 in HL60 cells1

Abstract: Aim: To investigate the mechanism underlying the killing effects of a novel amphipathic photosensitizer, disulfonated diphthalimidomethyl phthalocyanine zinc (ZnPcS2P2), mediated photodynamic therapy (ZnPc‐PDT) in human myelogenous leukemia HL60 cells. Methods: After incubation for 5 h with 0.5 μmol/L ZnPcS2P2, the HL60 cells were exposed to a light source of 670 nm wavelength. Thereafter, the cells were detected at different time intervals after PDT. The characteristics of apoptosis were detected by observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…Similar results were also described recently for another photosensitizer, disulfonated diphthalimidomethyl phthalocyanine zinc (ZnPcS 2 P 2 ) [23]. Additionally, we observed that the irradiated riboflavin leads to leukaemia cell proliferation inhibition as shown by the activation of p21 and downregulation of PCNA.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also described recently for another photosensitizer, disulfonated diphthalimidomethyl phthalocyanine zinc (ZnPcS 2 P 2 ) [23]. Additionally, we observed that the irradiated riboflavin leads to leukaemia cell proliferation inhibition as shown by the activation of p21 and downregulation of PCNA.…”
Section: Discussionsupporting
confidence: 89%
“…The drop in the intermembrane potential mainly detected in the perinuclear mitochondria can be related to the intracellular localization of RB, being predominantly present in the perinuclear cytoplasmic region. The structural alterations are consistent with the induction of apoptotic cell death; in fact, the ballooning of mitochondria, with disruption of the cristae and internal organelle structure, we found by Xuorescence and electron microscopy at 48 h p-t was also described by Luchetti et al (2006) for apoptotic U937 promonocytic leukemia cells exposed to UV-B, and by Huang et al (2005) for HL60 cells upon photosensitization. Similarly swollen mitochondria were described by Shen et al (2002) in apoptotic esophageal carci- Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Zinc can sensitize cancer cells for physical agents; disulfonated diphthalimidomethyl phthalocyanine zinc (ZnPcS 2 P 2 ) has been used to induce mitochondria‐dependent apoptosis in K562 and HL60 cells as a novel amphipathic photosensitizer (Huang et al., 2005a, b). Exposure to H 2 O 2 increased DNA fragmentation in K562 cells, preincubated with ZnSO 4 , indicating that zinc sensitized cancer cells to genotoxic agents in contrary to normal cells.…”
Section: Discussionmentioning
confidence: 99%